Alice in Wonderland - Geronimi, Clyde; Luske, Hamilton S.; Jackson, Wilfred; Wallace, Oliver, 1887-1963; Beaumont, Kathryn; Wynn, Ed, 1886-1966; Haydn, Richard, 1905-1985; Carroll, Lewis, 1832-1898.; Walt Disney Productions; Walt Disney Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) (Burbank, Calif. : Walt Disney Home Entertainment, 2004)
Disney's animated version of Lewis Carroll's fable tells the story of Alice, who falls down a rabbit hole & ends up in Wonderland with the Mad Hatter, the Cheshire Cat and the Queen of Hearts.
Originally released as a motion picture in 1951.
Features: additionally releases material, short film "Thru the mirror," "Operation wonderland" featurette, interactive features, sing along songs, character card game.
Animation, Milt Kahl; editor, Lloyd Richardson; music, Oliver Wallace.
Voices: Kathryn Beaumont, Ed Wynn, Richard Haydn, Sterling Holloway, Jerry Colonna, Verna Felton, Bill Thompson.
MPAA rating: G.
DVDs, Dolby digital 5.1 surround.
Keywords: Carroll, Lewis, -- 1832-1898 -- Film and video adaptations; Children's films; Video recordings for the hearing impaired; Based on the book; Feature films; Fantasy films; Animated films